2020
DOI: 10.1016/j.foodchem.2020.127334
|View full text |Cite
|
Sign up to set email alerts
|

Lithium contamination of honeybee products and its accumulation in brood as a consequence of anti-varroa treatment

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…Lithium concentration decreased in all body parts of the bees from day 4 post-treatment ( Table 2 , Figure 2 ). This pattern may be consistent with the findings of Prešern and colleagues , who revealed that in bee larvae, lithium level started to drop on day 3 post-treatment [ 15 ]. By day 22 post-treatment, lithium level showed full recovery to the pre-treatment control level (0.15 mg kg −1 on average; Figure 2 ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Lithium concentration decreased in all body parts of the bees from day 4 post-treatment ( Table 2 , Figure 2 ). This pattern may be consistent with the findings of Prešern and colleagues , who revealed that in bee larvae, lithium level started to drop on day 3 post-treatment [ 15 ]. By day 22 post-treatment, lithium level showed full recovery to the pre-treatment control level (0.15 mg kg −1 on average; Figure 2 ).…”
Section: Resultssupporting
confidence: 92%
“…Feeding lithium syrup at a concentration (25 mM) applied in earlier studies [ 9 , 15 , 20 ] resulted in an average lithium peak of 130.13 mg kg −1 (average of the hives) in bees’ bodies (thorax and abdomen), with an absolute maximum value of 167.71 mg kg −1 in hive 1, on day 4. Lithium concentration decreased in all body parts of the bees from day 4 post-treatment ( Table 2 , Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calculating slope within moving window allows taking into the account both excitation and suppression of normal activity, as demonstrated on fish data or insect olfaction [4] , with length of the window adjustable to the rate of firing. We have adopted the method for the purpose of evaluating the impact of bioactive substance – in our case lithium [3] – on the honeybee colony. With the proposed method the investigator avoids absolute numbers in natural mortality and thus makes colonies comparable among themselves.…”
Section: Methods Detailsmentioning
confidence: 99%